Yield-Line solutions for flexural failure of flat slabs on columns of different shapes. (June 2022) - Zhang, Wei; Xue, Jianyang; Xu, Jinjun; Xi, Xingwang; Li, Baoxin; Liu, Kang
Abstract: There are two failure modes of slab–column connections, flexural and punching shear. However, when the tensile reinforcement ratio in the slab is low, the failure mode of the slab is difficult to distinguish, because the slab may fail in flexural before the punching shear failure occurs. To study the flexural failure of flat slabs on special-shaped columns (cruciform, L-shaped, T-shaped), the ultimate bearing capacity of slab–special-shaped column connections considering corner lever effect under vertical concentrated load was deduced and predicted by using yield-line theory. The correctness of the theoretical solution was verified by comparison with the experimental results. In addition, the effects of column section shape, column limb length to thickness ratio ( c 2 / c 1 ) and reinforcement ratio on flexural capacity were studied. The results show that the column section shape and the c 2 / c 1 have little influence on the flexural capacity of the slab, but the reinforcement ratio will change the failure mode of the slab-column connections. When the reinforcement ratio was less than 0.8%, the failure mode of slab–special-shaped column connections was main flexural failure..